Child care in action school age - Hoffman, Sara McCormack ([s.l.] : Thomson Delmar Learning, 2005)
Provides information specific to school age child care , development and program management
System requirement : Windows Pentium computer ; Windows 98/2000/XP/2003 ; CD-ROM drive ; Acrobat Reader ; Macromedia Flash Player
Keywords: Child care; School - age child care; School children; Child development